Production of Third Generation Bioethanol via Hydrolysis of Macroalgae (Seaweed) Using Heterogeneous Catalyst - Lee , Keat Teong; Mohamed, Abdul Rahman; Abdullah, Ahmad Zuhairi (Universiti Sains Malaysia, 2013)
The efficacy of red macroalgae Eucheuma cottonii (EC) as feedstock for third-generation bioethanol production was evaluated. Dowex (TM) Dr-G8 was explored as a potential solid catalyst to hydrolyzed carbohydrates from EC or macroalgae extract (ME) and pretreatment of macroalgae cellulosic residue (MCR), to fermentable sugars prior to fermentation process. The highest total sugars were produced at 98.7 g/L when 16% of the ME was treated under the optimum conditions of solid acid hydrolysis (8% (w/v) Dowex (TM) Dr-G8. 120 "C, 1 h) and 2% pretreated MCR (P-MCR) treated by enzymatic hydrolysis (pH 4.8. 50 ®C, 30 h). Atwo-stream process resulted in 11.6 g/L of bioethanol from the fermentation of ME hydrolysates and 11.7 g/L from prehydrolysis and simultaneous saccharification and fermentation of P-MCR. The fixed price of bioethanol obtained from the EC is competitive with that obtained from other feedstocks.